(untitled) (Diametros, 2015)
The aim of the present article is to consider the shortcomings of the physicalist rainfall example set forth by Aristotle in Physics II.8. I first outline the ancient physicalist account of the coming-to-be of natural organisms and the accompanying rejection of the teleological character of such processes. Then I examine the rainfall example itself. The fundamental difficulty is that rainfall does not appear to have a proper nature. Hence it is not natural in the strict sense and cannot be used in arguments either for or against natural teleology. Rainfall can at most have an end in a weak sense, which makes it inadequate as a paradigm. Furthermore, the physicalist conception of action for an end is itself flawed. I argue that they construe it anthropomorphically and falsely presuppose a symmetry between coming-to-be and ceasing-to-be. I would like to thank Hasse Hamalainen and Marcin Karas for looking at earlier drafts of this paper. I am also especially grateful for the numerous remarks and suggestions of three anonymous referees.